Weed Management in Late Kharif Cluster Bean (Cyamopsis tetragonoloba (L.) Taub) and its Impact on Crop Growth and Yield - Saras, Piyush Kumar; Patel, B. D.; Parmar, Sejal K.; Patel, R. B. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during kharif 2013-2014 at DWSR-Anand Centre, Anand Agricultural University, Anand (Gujarat) where four herbicides either as sole, integrated with hand weeding (HW) or sequentially applied were evaluated for efficacies of the herbicides on controlling weeds, their influences on yield and production economics on cluster bean (Cyamopsis tetragonoloba (L.) Taub) variety was Gujarat Gaur 1 (GG-1). The dominant weed species among monocot weeds were Echinochola crusgalli, Eleusine indica, Commelina benghalensis, Digitaria sanguinalis, Eragrostis major, Cynodon dactylon and Cyperus rotundus,however amongdicot weed species Digera arvensis, Phyllanthus niruri, Amaranthus viridis, Oldenlandia umbellate, Euphorbia hirta and Spergula arvensis were observed during the growing season. Weed dry weight of monocot and dicot weed was the lowest in intercultering followed by hand weeding carried out at 20 and 40 days after sowing at 25 and 50 days after sowing and at harvest which remain at par with integrated weed management approach treatment pendimethalin+imazethapyr (pre-mixed) @ 800 g ha-1 pre emergence followed by hand weeding at 30 days after sowing. Maximum weed control efficiency was observed with the intercultering followed by hand weeding at 20 and 40 days after sowing. This treatment also recorded higher yield attributes and seed and stover yield (16.55 and 49.36 q ha-1). And gave maximum net monetary returns and B:C ratio (Rs. 59404 ha-1 and 2.97, respectively).